PENGARUH PENYULUHAN GIZI MENGGUNAKAN MEDIA WAYANG DAN BOOKLET TERHADAP PENGETAHUAN 10 PESAN GIZI SEIMBANG PADA ANAK SEKOLAH DASAR - Maulida Amalia Utami (2020)
Poor nutritional problems in elementary school children is one of the lack of less education to know and understand the importance of nutrition in daily life. Various ways can be done to improve knowledge about nutrition one of them is given learning through nutrition counseling using puppet media and booklets. The use of puppet media and booklets in nutrition counseling because the information presented is complete, practical and more interesting in delivering balanced nutrition message. This research aims to determine the influence of nutritional counseling using puppet media and booklet on the knowledge of 10 balanced nutritional messages in elementary school children. The type of research used is Quasi Experiment research with pretest-posttest with control group. The population of this research study is a grade V subsidiary of SDN Mekar Mukti 06 as many as 46 people and balanced nutritional knowledge obtained by a questionnaire. With the sampling techniques used are purposive sampling. Data analysis using the Wilcoxon and Mann-Whitney Test. The results of the data found that there was an influence of nutrition counseling using puppet media and a booklet for balanced nutritional knowledge in elementary school children (p = 0,000 <0.05) and the influence of nutritional counseling before and after intervention in both treatment groups (p = 0.006 <0, 05). Nutritional counseling using puppet media and booklets affects knowledge. There is a difference in the improvement of nutritional knowledge before and after counseling in puppet group and booklets.